Sponsoring a Race to the Top : The Case for Results-Based Intergovernmental Finance for Merit Goods - Shah, Anwar (World Bank, Washington, DC, 2014)
Intergovernmental finance is a significant source of sub-national finance in most countries. In both industrial and developing countries, formula based "manna from heaven" general purpose transfers dominate but co-exist with highly intrusive micro-managed "command and control" specific purpose transfers. Both these types of transfers undermine political and fiscal accountability. Reforms to bring in design elements that incorporate incentives for results-based accountability are resisted by both donors and recipients alike. This is because the donors perceive such reforms as attempts at chipping away at their powers and recipients fear such programs will be intrusive. This paper presents conceptual and practical underpinnings of grant designs that could further simplicity, objectivity, and local autonomy objectives while furthering citizen-centric results-based accountability. The paper further highlights a few notable recent initiatives in both industrial and developing countries that embrace such directions for reform. The paper concludes that results-based intergovernmental finance offers significant potential to minimize tradeoffs between local autonomy and accountability while furthering access to merit goods.